A grain of wheat - Agnew, Elizabeth Jane (My University, 1900)
Introduction: There is, perhaps, no cereal so universally used as wheat; and not only is it now known almost every where, but even before history began to leave us records of the products of the past ages we find that the people of Europe had cultivated wheat, as samples have been recovered from the locustrine dwellings of Switzerland. Also, the Israelites in Egypt, ate leavened bread; the prophet Samuel, in the book which bears his name speaks of the “wheat harvest;” and the psalmist David, in his praise to God for His blessings upon the kingdom sings, “He maketh peace in thy borders and filleth thee with the finest of the wheat.” Ever since the far off days when our fore fathers first found the wild cereals, or began to cultivate them, men have known that food prepared from wheat would support life and strength better than any other single food except milk. The diet of the poor in India and China often consisted entirely of wheat or millet cakes or rice; and, altho in our own land the ease with which we can get other foods makes the use of wheat products of less importance, there are still many districts in Europe where the people eat very little else. As we have before intimated, the history of wheat began in the remote ages. Asia was supposed to have introduced it into Egypt; Demeter into Greece, and Emporer Chin-Wong into China, about 3000 years before Christ. The first wheat raised in the “New World” was sown by the Spaniards on the island of Isabella, in January, 1494, and on March 30th, the ears were gathered. The foundation of the wheat harvest of Mexico is said to have been three or four grains carefully cultivated in 1530, and preserved by a slave of Cortez. In 1611, the first wheat appeared to have been sown in Virginia. In 1626, samples of wheat grown in the Dutch colony at New Netherlands were shown in Holland. It is probable that wheat was sown in the Plymouth colony prior to 1629, tho we find no record of it; and in that self-same year wheat was ordered from England to be used as seed. In 1718, wheat was introduced into the valley of the Mississippi by the “Western Company.” In 1799, it was among the cultivated crops of the Pimos Indians of the Gila River, New Mexico.
Citation: Agnew, Elizabeth Jane. A grain of wheat. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Wheat; Milling; Flour; Bread; Nutrition; Theses